2017
DOI: 10.1016/j.jct.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the thermodynamic properties of water from the speed of sound

Abstract: Thermodynamic properties of compressed liquids may be obtained from measurements of the speed of sound by means of thermodynamic integration subject to initial values of density and isobaric specific heat capacity along a single low-pressure isobar. In this paper, we present an analysis of the errors in the derived properties arising from perturbations in both the speedof-sound surface and the initial values. These errors are described in first order by a pair of partial differential equations that we integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 8 publications
(20 reference statements)
3
31
0
Order By: Relevance
“…The method was first used by Davis and Gordon [45] for mercury and improved by Sun et al [46]. The algorithm used [47] and the uncertainty of the method have also been studied in detail in a recent paper [48].…”
Section: Derived Thermodynamic Propertiesmentioning
confidence: 99%
“…The method was first used by Davis and Gordon [45] for mercury and improved by Sun et al [46]. The algorithm used [47] and the uncertainty of the method have also been studied in detail in a recent paper [48].…”
Section: Derived Thermodynamic Propertiesmentioning
confidence: 99%
“…This potentiality, specific to speed of sound, has been used for obtaining isentropic and isothermal compressibility coefficients of a large number of pure liquids and liquid mixtures. In particular, Kell and Whalley and, recently, Trusler and Lemmon calculated the thermodynamic properties of water from the speed of sound, whereas Davis and Gordon used this method for estimating the compressibility of liquid mercury at ultrahigh pressure (GPa). Muringer et al followed by several other groups investigated the compressibility of hydrocarbons from ultrasonic speed measurements.…”
Section: Introductionmentioning
confidence: 99%
“…This method is called thermodynamic integration and was originally devised by Davis and Gordon in 1967. Ever since, it has been applied by many authors, and various algorithms have been suggested to integrate the system of partial differential equations, e.g., refs . Because all thermodynamic properties can be calculated in the domain of the speed-of-sound measurements, the thermodynamic integration provides a means for generating comprehensive data sets that can be used as part of the database for developing wide-ranging Helmholtz energy formulations for pure fluids and mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…For the density, accurate values at low pressures are available for many fluids, but data for the isobaric heat capacity are often not available or are associated with large uncertainties. Only for fluids such as water, for which the properties at ambient pressure are known very accurately, can this method be adopted. , Another possibility is to derive initial values for the specific isobaric heat capacity c p from very accurate speed-of-sound and density data sets at low pressure by the thermodynamic relation in which T is the thermodynamic temperature, ρ is density, p is pressure, and c denotes the speed of sound. When the density data are correlated accurately as a function of temperature and pressure, the partial derivatives along the initial isobar of the integration can easily be calculated, and precise values of the specific isobaric heat capacity can be derived by eq .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation